Răspuns :
(1-√3)²+(1+√3)² - (1-√3)(1+√3)= ?
(1-√3)²= 1-2√3+3 = 4-2√3
(1+√3)² = 1+2√3+3= 4+2√3
(1-√3)(1+√3)= 1²-√3² = 1-3=-2
(1-√3)²+(1+√3)² - (1-√3)(1+√3)=
4-2√3+4+2√3-(-2)=
4+4+2=10
(1-√3)²= 1-2√3+3 = 4-2√3
(1+√3)² = 1+2√3+3= 4+2√3
(1-√3)(1+√3)= 1²-√3² = 1-3=-2
(1-√3)²+(1+√3)² - (1-√3)(1+√3)=
4-2√3+4+2√3-(-2)=
4+4+2=10
[tex](1- \sqrt{3} )^2+(1+ \sqrt{3} )^2-(1- \sqrt{3}) (1+ \sqrt{3} )= \\ =1^2-2 \cdot 1 \cdot \sqrt{3} + \sqrt{3^2} +1^2+2 \cdot1 \cdot \sqrt{3} + \sqrt{3^2} -1+3= \\ =1-2 \sqrt{3} +3+1+2 \sqrt{3} +3-1+3=10[/tex]